Analisis Harga Pokok Produksi untuk Menentukan Harga Jual - Sri Wahyuni; Gatot Wahyu Nugroho; Elan Eriswanto (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to determine the calculation of the cost of goods produced using the Full Costing method, to determine the calculation of the cost of goods produced using the Variable Costing method, and to calculate the difference between the two methods on the cost of goods produced and its effect on the selling price. The method used in this research is a qualitative method with a descriptive approach. This research has three elements of the social situation, namely CV. Nj Food Industries jl.cikiray kaler, sukamanah, kec. Cisaat, sukabumi district 43152 (place), CV. Nj Foods Finance Department (Actors), and Analysis of the cost of production to determine the selling price (Activities). Data collection techniques in this study are observation, interviews, documentation and literature study. The data analysis techniques used in this research are data reduction, data display, and Conclusing Drawing / verification. The results of this study indicate that in determining the cost of goods produced at CV Nj. Food Industries there are still costs that he has not included such as depreciation costs, transportation costs and others. Then there are differences in the calculation of the cost of goods manufactured by CV Nj Food Industries using the full costing and variable costing methods.